Case report: Physical findings, physical therapy practice, and characteristics of disability of activities of daily living caused by obturator nerve palsy after neurotmesis - Shima, Daichi; Kinoshita, Tokio; Umemoto, Yasunori; Yasuoka, Yoshinori; Hashizaki, Takamasa; Asaeda, Makoto; Nishimura, Yukihide; Yahata, Tamaki; Shimoe, Takashi; Tajima, Fumihiro (Frontiers in Neurology, 2023)
Abstract The obturator nerve originates from the lumbar plexus and innervates sensation in the thigh and movement of the adductor muscle group of the hip. Reports on physical therapy for patients with obturator nerve injuries have been limited due to insufficiency injuries, and there have been no reports on rehabilitation after neurotmesis. Furthermore, there are no reports on the status of activities of daily living (ADL) and details of physical therapy in patients with adductor muscle group paralysis. In this study, we report on a patient with adductor paralysis due to obturator neurotmesis, including the clinical symptoms, characteristics of ADL impairment, and effective movement instruction. The patient is a woman in her 40s who underwent a total laparoscopic hysterectomy, bilateral adnexectomy, and pelvic lymph node dissection for uterine cancer (endometrial carcinoma, grade 2). During pelvic lymph node dissection, she developed an obturator nerve injury. She underwent nerve grafting during the same surgery by the microsurgeon. The donor nerve was the ipsilateral sural nerve, and the graft length was 3cm. Postoperatively, due to obturator nerve palsy, a manual muscle test revealed 1 adductor magnus muscle, 1 pectineus muscle, 0 adductor longs muscle, 0 adductor brevis muscle, and 0 gracilis muscle. On postoperative day 6, the patient was independently performing ADL; however, she was at risk of falling toward the affected side when putting on and taking off her shoes while standing on the affected leg. The patient was discharged on postoperative day 8. Through this case, we clarified the ADL impairment of a patient with adductor muscle palsy following obturator neurotmesis, and motion instruction was effective as physical therapy for this disability. This case suggests that movement instruction is important for acute rehabilitation therapy for patients with hip adductor muscle groups with obturator neurotmesis.